A NuSTAR and Swift view of the hard state of MAXI J1813-095 - Jiang, Jiachen; Buisson, Douglas J. K.; Dauser, Thomas; Fabian, Andrew C.; Furst, Felix; Gallo, Luigi C.; Harrison, Fiona A.; Parker, Michael L.; Steiner, James F.; Tomsick, John A.; Ubach, Santiago; Walton, Dominic J. (Monthly Notices of the Royal Astronomical Society, 2022)
We present an analysis of the NuSTAR and Swift spectra of the black hole candidate MAXI J1813-095 in a failed-transition outburst in 2018. The NuSTAR observations show evidence of reflected emission from the inner region of the accretion disc. By modelling the reflection component in the spectra, we find a disc inner radius of Rin < 7 rg. This result suggests that either a slightly truncated disc or a non-truncated disc forms at a few per cent of the Eddington limit in MAXI J1813-095. Our best-fitting reflection models indicate that the geometry of the innermost accretion remains consistent during the period of NuSTAR observations. The spectral variability of MAXI J1813-095 from multi-epoch observations is dominated by the variable photon index of the Comptonization emission.
CRIS-Team Scopus Importer:2022-07-15
Keywords: accretion; accretion discs; black hole physics; X-rays: binaries